Comparison of continuous and pulsed wave lasers in keyhole welding of stainless‑steel to aluminium - Coroado, Julio; Ganguly, Supriyo; Williams, Stewart W.; Suder, Wojciech; Meco, Sonia; Pardal, Goncalo (Springer, 2021)
A continuous wave (CW) and a nanosecond pulsed wave (PW) lasers were used to join 1-mm thick sheets of SS304L (SS) austenitic stainless-steel to AA5251 (Al) aluminium alloy in an overlap joint configuration. The weld shape (penetration depth and width), intermetallic compounds concentration, weld quality (cracking and porosity) and mechanical strength were correlated with the process energy and compared between each laser temporal mode. Successful CW joints were produced with the SS sheet on top of the Al, but the opposite configuration revealed to be impossible for the range of parameters tested. The PW joints were successful with the Al sheet on top of SS, but all the joints cracked at the interface when the opposite configuration was used. The mechanical tests showed that even though it is possible to achieve higher tensile shear load in CW welds due to the larger bonding area, the tensile shear strength revealed to be almost 5 × higher for PW welds at similar applied energy.
Keywords: Dissimilar metal joining; Keyhole laser welding; Intermetallic compounds; Aluminium; Stainless-steel